STRATEGI PENGEMBANGAN WISATA PULAU TEGAL MAS DESA GEBANG PESAWARAN LAMPUNG PASCA PANDEMI (Studi pada Dinas Pariwisata Kabupaten Pesawaran) - Khotivi, Dewi Anggi; Kagungan, Dian; Meiliyana, Meiliyana (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2025)
A region has its own potential. Tourism plays an important role in regional income and the welfare of the surrounding community, therefore in every region requires the development of tourism in order to always progress. This study aims to find out the strategy carried out by the Tourism Office of Airplanean Besarma Regency, Tegal Mas Island Tourism Object and other agencies to increase the number of tourists so that they experience an increase in PAD and the income of the surrounding community and identify driving and inhibiting factors. The method used is a qualitative method with the theory of salusu and measuring tools SWOT analysis. Data collection techniques in the form of interviews, documentation and observation. Based on the results of the analysis carried out by researchers that the Tegal Mas Island Tourism Object has the potential to be able to attract tourists, however there are still obstacles such as lack of promotion, high travel costs and lack of cooperation between the government and the private sector. The role of the Tourism Office is very important to participate in the development of Tegal Mas tourism in order to increase PAD and Community Welfare.